ICHNOTAXONOMY AND ETHOLOGY OF BORINGS IN SHALLOW-MARINE BENTHIC FORAMINIFERS FROM THE MAASTRICHTIAN AND EOCENEOF NORTHWESTERN AND SOUTHWESTERN TURKEY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Larger benthic foraminiferal tests from the Maastrichtian and Eocene of western Turkey contain a large variety of borings. Two ichnospecies are defined. Maeandropolydora osmaneliensis isp. nov. in tests of Orbitoides is distinguished by a tube, winding sinuously in an irregular manner. This boring was formed by a foraging parasite or scavenger, where the tracemaker specifically exploited certain parts of its substrate. Trypanites helicus isp. nov. in tests of Nummulites is characterized by its tube coiled into a spiral. The boring is interpreted as a dwelling trace. As the boring may be considered to have both idiomorphic and stenomorphic features, it represents an ethological and taxonomic dilemma. To avoid inherent subjectivity within taxonomic classifications, we suggest the exclusion of ethological interpretations from diagnoses. The occurrence of borings may affect the preservational potential of the foraminiferal tests, and thus on the outcome of palaeoenvironmental analyses.